Mechanisms behind corticosteroid resistance in obesity-induced airway inflammation – a review - Włodarczyk, Piotr; Sułkowska, Ada; Matshaba, Vimbisoyashe Ivy; Czerwiński, Filip; Piotrowski, Igor (Journal of Medical Science, 2024)
Obese non-eosinophilic asthma is defined as more severe asthma with severe symptoms, moderate airway hyperresponsiveness, elevated blood neutrophils, elevated biomarkers of non-type-2 inflammation, and low responsiveness to inhaled corticosteroids. Increased BMI is associated with a faster decline of FEV1 and FVC in adult asthmatics. The increased leptin concentration is connected with asthma by its ability to induce airway remodelling. Obesity-associated airway hyperresponsiveness is possibly mediated by NLRP3 inflammasome, IL-1β, and ILC3 cells. Increased sputum expression of NLRP3 and IL-1β is linked with increased neutrophil numbers, airflow obstruction, and worse asthma control. Accumulation of proinflammatory cytokines like IL-17, IL-1β, TNF-α, and reactive oxygen and nitrogen species contributes to corticosteroid resistance in obese asthmatics. The processes on the cellular level leading to steroid hyporesponsiveness include a reduced level of glucocorticoid receptor (GR) isoform - GR-α, the dysregulation of the isoforms concentration GR-α/GR-β, increased phosphorylation at Ser 226, and decreased expression of histone deacetylase 2. The best way to improve sensitivity to corticosteroids in this patient group is weight loss. Bariatric surgery is the most effective solution. However, patients may find it beneficial to implement lifestyle changes or to use GLP-1 analogues. Identifying underlying mechanisms of resistance to corticosteroids in obese asthmatics will allow for more effective asthma treatment in the future and could lead to long-term reduction of treatment costs.
Keywords: Obesity related asthma; corticosteroid resistance; NLRP3 inflammasome; glucocorticoid receptor; bariatric surgery; GLP-1 analogs